Social media in undergraduate medical education: A systematic review. Issue 11 (4th June 2021) - Guckian, Jonathan; Utukuri, Mrudula; Asif, Aqua; Burton, Oliver; Adeyoju, Joshua; Oumeziane, Adam; Chu, Timothy; Rees, Eliot L.
Abstract: Introduction: There are over 3.81 billion worldwide active social media (SoMe) users. SoMe are ubiquitous in medical education, with roles across undergraduate programmes, including professionalism, blended learning, well being and mentoring. Previous systematic reviews took place before recent explosions in SoMe popularity and revealed a paucity of high‐quality empirical studies assessing its effectiveness in medical education. This review aimed to synthesise evidence regarding SoMe interventions in undergraduate medical education, to identify features associated with positive and negative outcomes. Methods: Authors searched 31 key terms through seven databases, in addition to references, citation and hand searching, between 16 June and 16 July 2020. Studies describing SoMe interventions and research on exposure to existing SoMe were included. Title, abstract and full paper screening were undertaken independently by two reviewers. Included papers were assessed for methodological quality using the Medical Education Research Study Quality Instrument (MERSQI) and/or the Standards for Reporting Qualitative Research (SRQR) instrument. Extracted data were synthesised using narrative synthesis. Results: 112 studies from 26 countries met inclusion criteria. Methodological quality of included studies had not significantly improved since 2013. Engagement and satisfaction with SoMe platforms in medical education are described. Students felt SoMe flattened hierarchies and improved communication with educators. SoMe use was associated with improvement in objective knowledge assessment scores and self‐reported clinical and professional performance, however evidence for long term knowledge retention was limited. SoMe use was occasionally linked to adverse impacts upon mental and physical health. Professionalism was heavily investigated and considered important, though generally negative correlations between SoMe use and medical professionalism may exist. Conclusions: Social media is enjoyable for students who may improve short term knowledge retention and can aid communication between learners and educators. However, higher‐quality study is required to identify longer‐term impact upon knowledge and skills, provide clarification on professionalism standards and protect against harms. Abstract : Two sides of the coin: With this systematic review, the authors synthesize evidence demonstrating how #SoMe can improve outcomes despite ongoing questions about professionalism